Metabolic Profile, Bioactivities, and Variations in the Chemical Constituents of Essential Oils of the Ferula Genus (Apiaceae) - Sonigra, Priyankaraj; Meena, Mukesh (Frontiers in Pharmacology, 2021)
The genus Ferula is the 3rd largest and a well-known genus of the Apiaceae family. It is categorized in tribe Peucedaneae and subtribe Ferulinae of the family. Up to now, about 180 Ferula species have been reported. The genus is mainly distributed in throughout central and South-West Asia (especially Iran and Afghanistan), far-East, North India and the Mediterranean area. The genus Ferula is characterized by the presence of oleo-gum-resins (asafoetida, sagapenum, galbanum, and ammoniacum) and their use in natural and conventional pharmaceuticals. The main phytochemicals present in the genus Ferula are as follows: coumarin, coumarin esters, sesquiterpenes, sesquiterpene lactones, monoterpene, monoterpene coumarins, prenylated coumarins, sulfur-containing compounds, phytoestrogen, flavonoids and carbohydrates. This genus is considered as a valuable group of medicinal plants due to very high biological and pharmacological uses of volatile oils (essential oils). Numerous biological activities are shown by the chemical components of the essential oils obtained from different Ferula species. Since, this genus included many bioactivities such as antimicrobial, insecticidal, antioxidant, cytotoxic, etc. therefore, researchers are getting more focused to this genus. However, several reviews are available on this particular genus, including information about the importance and uses of all the phytochemicals found in the species of Ferula. Despite this, no such review has been published yet that specifically provides information about the biological activities of Ferula-derived EOs. Therefore, the present review has been conducted to provide important information about the chemical profile, factors affecting the chemical composition and biological activities of essential oils of Ferula species.